Terceirização no ramo hoteleiro de Foz do Iguaçu: flexibilização ou precarização das relações de trabalho? - Wrobel, Fernando de Nadai (2022)
The capital through flexible accumulation seeks ways to reduce its expenses and make the company leaner, in this sense the unrestricted outsourcing presents itself as the ideal tool for this purpose, however with a high cost for outsourced employees, who suffer the effects of the precariousness of the employment contract. In the present work, concepts of labor law were analyzed, such as the employment relationship, union framework, collective conventions and agreements, the concept and characteristics of outsourcing, the systems of labor organization, flexible accumulation, the path taken by the legislation and labor jurisprudence in relation to outsourcing, and finally a comparison between collective instruments of two categories, making a comparison between direct employees and outsourced employees, in order to demonstrate whether there is precarization of the labor contract through outsourcing. The present study adopted bibliographical and documental research.